Offset Adjustment Mechanism and Rigid-flexible Coupling Analysis Method for Spatial Ultra-thin Paper Tape - Gan Shengyong; Hong Guanghuai; Zhou Changjiang (Jixie chuandong)
Taking the ultra-high-speed cigarette making and tipping machine as object， the offset adjustment and rigid-flexible coupling analysis method of the ultra-thin paper tape is studied. By using the spatial flattening projection method， the effects of the spacing of the inclined rollers or the angle of the inclined pads on the paper tape offset is investigated. The kinematics and dynamical models of the ultra-thin paper tape are built， and the elastic modulus of the paper tape is measured. Herein， a rigid-flexible coupling model of offset adjustment mechanism is developed by dispersing the paper tape into flexible body units and the roller into rigid body units. The results show that the numerical and measured lateral offsets at the output tape are consistent. These findings can be available for the offset parameters optimization and smooth conveying of the ultra-thin paper tape.